Robotic arms for hyperpolarization-enhanced NMR - Kirill Sheberstov; Erik Van Dyke; Jingyan Xu; Raphael Kircher; Liubov Chuchkova; Yinan Hu; Sulaiman Alvi; Dmitry Budker; Danila A. Barskiy (Journal of Magnetic Resonance Open, 2025)
Optimization of nuclear spin hyperpolarization experiments often require varying one system parameter at a time (or several parameters in a nontrivial manner) as well as multiple repetitions of signal measurements. Use of automated robotic systems can significantly streamline this optimization process, accelerating data acquisition and improving reproducibility in the long term. In this work we show an exemplary system built on open-source components and demonstrate several benchtop and ultralow-field NMR experiments employing photo-CIDNP and SABRE-derived hyperpolarization. This work illustrates that open-source platforms employing benchtop NMR and robotic systems built in a modular manner with remote operation allow the implementation of various unconventional experiments in a reproducible manner.